Simultaneous removal of chromotrope 2B and radionuclides from mixed radioactive process wastewater using organo-bentonite - Shakir, Kamal; Ghoneimy, Hussein Fouad; Hennawy, Ibtisam Tadros; Elkafrawy, Ahmed Faouzy; Beheir, Shokry Gad Elrab; Refaat, Mamdoh (European Journal of Chemistry, 2011)
The simultaneous removal of cationic radionuclides, 137Cs(I), 60Co(II) and 152+154Eu(III), and a chemically toxic anionic pollutant, the analytical reagent chromotrope 2B (C2B), from simulated mixed radioactive process wastewater (MRPWW) has been investigated using bentonite modified with cetyltrimethylammonium bromide. Modification was confirmed by elemental analysis, X-ray diffraction and infrared spectroscopy. Bentonite partially modified to 78% of the cation exchange capacity (PMB) was found capable to adsorb adequately both C2B and the radionuclides from aqueous solutions. Detailed batch kinetics and isotherm studies for removal of C2B singly and the radionuclides simultaneously were performed. The C2B and radionuclides kinetics conform to pseudo-first-order rate equation and the adsorption isotherms are treated with Freundlich and Langmuir models. Thermodynamic parameters were evaluated. Results suggest physisorption and ion-exchange as the principal uptake mechanism for C2B and the radionuclides, respectively. High simultaneous removal was obtained for C2B (≈ 100%) and each of the test radionuclides (>99%) from the simulated MRPWW.